Safety risks with investigational drugs: Pharmacy practices and perceptions in the veterans affairs health system. (June 2015) - Cruz, Jennifer L.; Brown, Jamie N.
Objectives: Rigorous practices for safe dispensing of investigational drugs are not standardized. This investigation sought to identify error-prevention processes utilized in the provision of investigational drug services (IDS) and to characterize pharmacists' perceptions about safety risks posed by investigational drugs. Methods: An electronic questionnaire was distributed to an audience of IDS pharmacists within the Veteran Affairs Health System. Multiple facets were examined including demographics, perceptions of medication safety, and standard processes used to support investigational drug protocols. Results: Twenty-one respondents (32.8% response rate) from the Northeast, Midwest, South, West, and Non-contiguous United States participated. The mean number of pharmacist full-time equivalents (FTEs) dedicated to the IDS was 0.77 per site with 0.2 technician FTEs. The mean number of active protocols was 22. Seventeen respondents (81%) indicated some level of concern for safety risks. Concerns related to the packaging of medications were expressed, most notably lack of product differentiation, expiration dating, barcodes, and choice of font size or color. Regarding medication safety practices, the majority of sites had specific procedures in place for storing and securing drug supply, temperature monitoring, and prescription labeling. Repackaging bulk items and proactive error-identification strategies were less common. Sixty-seven percent of respondents reported that an independent double check was not routinely performed. Conclusions: Medication safety concerns exist among pharmacists in an investigational drug service; however, a variety of measures have been employed to improve medication safety practices. Best practices for the safe dispensing of investigational medications should be developed in order to standardize these error-prevention strategies.